Interpretacja Przemienienia Jezusa. Część 2: Złota epoka literatury patrystycznej - Mejzner, Miroslaw (Vox Patrum, 2022)
The aim of the article is to compare the interpretation of the transfiguration of Jesus in the texts of four Church Fathers from the turn of the fourth and fifth centuries (John Chrysostom, Proclus of Constantinople, Augustine and Jerome). Crucial attention is paid to detailed content elements, contained in the Gospel accounts. The analysis of the interpretation made by selected authors reveals the close connection between the theological problems of the age (e.g. Trinitarian, Christological, Eschatological issues) and exegetical methods and approaches.